Examining the Belief on God and Higher Power through Mental Status and Mental Functioning of Recovering Addicts of Kolkata, India - Tinni Dutta; Disha Halder (Unisia, 2021)
In the present day there is a rapid growing interest in the arena of Psycho-spirituality and Mental Health. We need to bear in mind that the spiritual is co-extensive with the religious conception. We identify what we call the spiritual life with a concern to acquire holiness and a sense of presence of God through prayer, meditation and yoga practices. Believe in God transform individual’s identity and enhance ego functioning and status of wellbeing.  The cosmic image of ‘The Tree of Life may have been intended to help man in diversity, which in the life of the mind is called the discovery of meaning’. (Needleman, J,1973). Victor Frankl as quoted by Mc Clone, K (2003) stated that substance abuse might be a response to a loss of direction within the individual. Loss of freedom is perceived as the addictive substance claims possession’. Keeping these in mind the author tries to examine the relationship between the mental status and mental functioning of the addicts who have believed in God and those who don’t believe. After welcoming the clients’ mental status examination was conducted.  Appearances and behavior were noted. Some questions were asked and responses were recorded.  Similarly, ego functions assessment was consisted of both observations and semi-structured interviews. Differences are found to be significant at both .05 and .01 level in case of mental status examination, in case of ego functioning it was significant only at .05 level. Results are indicative of recovering addicts who believe in God would see the colorful aspect of life than who don’t believe in God. They adopt a flexible approach for desired success in lives.